Perlindungan Pekerja Migran Indonesia dalam Kerangka Keamanan Manusia - Dhanny Safitri; Ali Abdullah Wibisono (Indonesian Perspective, 2023)
Migration of workers is an important economic activity for both receiving and sending countries. However, apart from the benefits that migrant workers bring, there are many vulnerabilities and insecurities they face such as physical and mental violence, unpaid wages, human trafficking, and others. In fact, freedom from fear, freedom from want, and to live with dignity is the right of every worker as an individual. Using a qualitative approach and the framework of human security concept, this article aims to analyze the efforts made by the Indonesian government in protecting its migrant workers. The study found that the government efforts has demonstrated the practice of human security principles and approaches in its strategies; however, there are still many challenges that need to be addressed.